Sall1 regulates cortical neurogenesis and laminar fate specification in mice: implications for neural abnormalities in Townes-Brocks syndrome - Susan J. Harrison; Ryuichi Nishinakamura; Kevin R. Jones; A. Paula Monaghan (The Company of Biologists, 2012)
SUMMARY Progenitor cells in the cerebral cortex undergo dynamic cellular and molecular changes during development. Sall1 is a putative transcription factor that is highly expressed in progenitor cells during development. In humans, the autosomal dominant developmental disorder Townes-Brocks syndrome (TBS) is associated with mutations of the SALL1 gene. TBS is characterized by renal, anal, limb and auditory abnormalities. Although neural deficits have not been recognized as a diagnostic characteristic of the disease, ∼10% of patients exhibit neural or behavioral abnormalities. We demonstrate that, in addition to being expressed in peripheral organs, Sall1 is robustly expressed in progenitor cells of the central nervous system in mice. Both classical- and conditional-knockout mouse studies indicate that the cerebral cortex is particularly sensitive to loss of Sall1. In the absence of Sall1, both the surface area and depth of the cerebral cortex were decreased at embryonic day 18.5 (E18.5). These deficiencies are associated with changes in progenitor cell properties during development. In early cortical progenitor cells, Sall1 promotes proliferative over neurogenic division, whereas, at later developmental stages, Sall1 regulates the production and differentiation of intermediate progenitor cells. Furthermore, Sall1 influences the temporal specification of cortical laminae. These findings present novel insights into the function of Sall1 in the developing mouse cortex and provide avenues for future research into potential neural deficits in individuals with TBS.